Species Richness and Diversity in Secondary Lowland Forest, Bintuni, Bird's Head Peninsula, West Papua, Indonesia - Rumayomi, Nimrod Agustinus Andyratnah; Murdjoko, Agustinus; Ungirwalu, Antoni; Mulyadi; Benu, Nithanel Mikael Hendrik (Jurnal Manajemen Hutan Tropika, 2024)
The tropical forest plays an important role in ecosystem services, yet anthropological activities have changed the ecological conditions. Thus, this research was designed to reveal the species richness and diversity in secondary forests, including lifeform alteration. The 50 perpendicular plots were placed in both forests, with 25 for each. The study revealed that the secondary forest represents a stage of ecological succession in which species richness and diversity decreased. Additionally, the composition of life forms in the secondary forest changed, with dominant herbs indicating a more dynamic vegetation due to shifting ecological conditions. Species classified as Threatened have disappeared due to human activities in the forest. However, the secondary forest has provided a habitat for certain species, including those with conservation status, such as Threatened or Extinct, to thrive and colonize. Approximately 15.7% of species exclusively thrive in secondary forests, including Antiaropsis uniflora C.C.Berg. Therefore, to promote sustainable forest management, this study suggests monitoring the species in secondary forests, particularly since the use of forests has traditionally been determined by local communities, including in restricted forest areas. Moreover, the local government could officially designate traditional forest use, thereby allowing restricted forests to be conserved as old-growth forests.